Local Wisdom of the Community Responding to Ulcer Disease - Ikhsan Fadilla; Muhammad AbdulRohman; Ary Apriandika; Muhammad Fikri; Rakhael Adji Muhammad; Martha Erina; Fahrul Rozi; Farid Aulia (Indonesian Journal of Medical Anthropology, 2023)
There are a number of interesting things to reveal regarding the local wisdom of the community about boils. People still believe that Pamali sits on a pillow and thinks that eating too many eggs will make you more susceptible to boils. This is obtained from personal experience and that of other people, so that people have even more confidence in these pamali. Utilizing plant leaves that have undergone processing by pounding, boiling, and roasting, the community still frequently practices local wisdom in the traditional treatment of ulcers. The use of materials from nature is based on one's own knowledge and experience, as well as knowledge and experience from others.